β-cell heterogeneity and molecular plasticity in type 2 diabetes: multi-omics perspectives and the role of gut microbiota - Ruchko, Evgeny; Chernysheva, Maria; Sokolov, Vasily; Starinnov, Zakhar; Sabirov, Marat; Vasiliev, Andrey (Frontiers in Cell and Developmental Biology, 2026)
Type 2 diabetes (T2D) is a complex metabolic disorder characterized by systemic insulin resistance and progressive deterioration of pancreatic β-cell function. Advances in single-cell transcriptomics, epigenomics, and spatial transcriptomics have delineated marked β-cell heterogeneity, revealing subpopulations with differential secretory capacity, stress resilience, and vulnerability to metabolic and immune-mediated insults. These high-resolution approaches have further identified disease-associated alterations in other islet endocrine cells, as well as in immune, stromal, and exocrine pancreatic compartments, highlighting the central role of intercellular signaling in T2D pathogenesis. Concurrently, microbiome research has elucidated mechanisms by which gut microbial composition and metabolic activity modulate glucose homeostasis and β-cell function through immunoregulatory pathways, maintenance of epithelial barrier integrity, and enteroendocrine signaling, notably via glucagon-like peptide-1 (GLP-1). Therapeutic strategies targeting the gut microbiota include conventional probiotics, prebiotics, and fecal microbiota transplantation, alongside emerging synthetic biology approaches employing genetically engineered probiotic strains to deliver bioactive molecules, including GLP-1, directly in the gut microenvironment. This review integrates current multi-omics and experimental evidence to provide a comprehensive framework for understanding β-cell molecular plasticity, microbiota-mediated metabolic regulation, and their intersection as potential therapeutic targets. Such integrative approaches offer prospects for the development of precision interventions aimed at preserving or restoring β-cell function in T2D.